Assessment of the Impact of the Crisis on New PPI Projects : Update Three - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Despite the financial and economic crisis, new private activity in infrastructure continues to take place in developing countries. New projects are still being tendered and brought to financial closure, but at a slower pace. Between July 2008 and March 2009, the rate of project closure fell 15 percent by investment compared to a similar period in the previous year. Investment commitments to private infrastructure projects showed some signs of recovery in the first months of 2009, but this recovery was driven by a few large priority projects in select countries. These projects were able to raise financing thanks to the backing of highly-rated sponsors and their priority status in their respective countries. The financial crisis has made financing (both debt and equity) more difficult to secure, and has hampered the ability of governments to maintain their financial commitments to private infrastructure projects. These projects are facing higher cost of financing a problem compounded by the lower demand for infrastructure services that is beginning to impact some sectors. As a result some planned private infrastructure projects are being delayed, restructured, and, to a lesser extent, cancelled. Transport is the worst affected sector so far, while the most affected group of countries are middle-income countries, especially in the Eastern Europe and Central Asia region.